Smarts : are we hardwired for success? - Martin, Chuck, 1949- (AMACOM, 2007)
"The Profile" shows readers how to identify their strengths, then leverage them in their careers, personal lives, etc., and offers tips for compensating for one's weaker abilities. The book also shows how to identify abilities of other people and help them succeed. Martin's firm, NFI Research, identifies and analyzes trends and attitudes in business, management and technology. The Institute's invitation-only membership represents 1,400 of the world's most renowned and innovative companies, including members from half of the Fortune 100 companies. The powerful combination of authors - a business expert, a psychologist, and a neuropsychologist - gives this book an unprecedented level of credibility.